Efficient clustering techniques on Hadoop and Spark. (4th June 2019) - Ghamdi, Sami Al; Fatta, Giuseppe Di
Clustering is an essential data mining technique that divides observations into groups where each group contains similar observations. K-means is one of the most popular clustering algorithms that has been used for over 50 years. Due to the current exponential growth of the data, it became a necessity to improve the efficiency and scalability of K-means even further to cope with large-scale datasets known as big data. This paper presents K-means optimisations using triangle inequality on two well-known distributed computing platforms: Hadoop and Spark. K-means variants that use triangle inequality usually require caching extra information from the previous iteration, which is a challenging task to achieve on Hadoop. Hence, this work introduces two methods to pass information from one iteration to the next on Hadoop to accelerate K-means. The experimental work shows that the efficiency of K-means on Hadoop and Spark can be significantly improved by using triangle inequality optimisations.